Django 2 Web Development Cookbook : 100 practical recipes on building scalable Python web apps with Django 2, 3rd Edition /: 100 practical recipes on building scalable Python web apps with Django 2, 3rd Edition. (2018) - Kronika, Jake; Bendoraitis, Aidas
No abstract available